General chemistry principles and modern applications - Petrucci, Ralph H.; Herring, F. Geoffrey 1939-; Madura, Jeffry; Bissonnette, Carey (Pearson, 2017)
General Chemistry: Principles and Modern Applications, is the most trusted book on the market recognized for its superior problems, lucid writing, and precision of argument and precise and detailed and treatment of the subject. The 11th edition offers enhanced hallmark features, new innovations and revised discussions that that respond to key market needs for detailed and modern treatment of organic chemistry, embracing the power of visual learning and conquering the challenges of effective problem solving and assessment.